Accountant's perceptions about the Exam of Sufficiency of CFC - DOI: http://dx.doi.org/10.16930/2237-7662/rccc.v15n45p49-62 - Galvão, Nadielli (2016)
The purpose of this study was to verify the accountant's perceptions about the realization of exam of sufficiency. The data was collected by a survey with accountants cadastrated in a group of accounting discussion in a social network. The instrument of collect data was compost with questions about the profile of respondents, their perceptions about the realization and test approach, as well as brought the opportunity of accountants stand out suggestions for improving evaluation. How main results are outstanding the fact that 81,82% of respondents believe that the exam bring professional valorization and 82,73% realize the exam help to select the professionals more qualified. 89,55% of answerer are in favor that the continuity of exam, but 53,61% believe that is necessary some improvements. The main recommendation indicated by respondents was the necessity a better adequation of the test to reality of organizations.